Effect of extrusion ratio on paraffinic mineral oil lubricant in cold forward extrusion - Mohd Hafis, Sulaiman; Mohd Ridzuan, Mohd Jamir; Imaduddin Helmi, Wan Nordin; Syahrullail, Samion, Dr. (American Institute of Physics, 2013)
Link to publisher's homepage at http://www.aip.org/